2018
DOI: 10.1071/rd17179
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status affects the microRNA profile of the hypothalamus of female sheep

Abstract: Recent studies on the seasonal regulation of the oestrous cycle in sheep have focussed mainly on the responses to photoperiod. However, the brain systems that control reproductive activity also respond to nutritional inputs, although the molecular mechanisms involved are not completely understood. One possibility is that small, non-coding RNAs, such as micro-RNAs (miRNAs), have significant influence. In the present study, the amounts and characteristics of miRNAs in hypothalamus from oestrous and anestrous ewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
2
7
0
Order By: Relevance
“…Studies have found that Kiss1R can transmit signals through Gαq/11, thereby regulating GnRH secretion . Our research has shown that downregulation of GnAQ expression causes the upregulation of a series of estrous‐related genes; this regulatory mechanism may be different from the regulatory mechanism of the photoperiod; GPR54/Kiss are expressed on GnRH and kisspeptin neurons in the hypothalamus and simultaneously belong to the upstream genes of GnAQ in the GnRH signaling pathway, which are also major regulators of the HPG axis, consistent with the results of this study. In the GnRH signaling pathway, GnAQ acts as a downstream gene of the GnRH receptor and is directly affected by this receptor; the downstream genes of PLC and PRKCB can combine with nerve calcium‐regulating protein inhibitors, leading to renal insufficiency .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Studies have found that Kiss1R can transmit signals through Gαq/11, thereby regulating GnRH secretion . Our research has shown that downregulation of GnAQ expression causes the upregulation of a series of estrous‐related genes; this regulatory mechanism may be different from the regulatory mechanism of the photoperiod; GPR54/Kiss are expressed on GnRH and kisspeptin neurons in the hypothalamus and simultaneously belong to the upstream genes of GnAQ in the GnRH signaling pathway, which are also major regulators of the HPG axis, consistent with the results of this study. In the GnRH signaling pathway, GnAQ acts as a downstream gene of the GnRH receptor and is directly affected by this receptor; the downstream genes of PLC and PRKCB can combine with nerve calcium‐regulating protein inhibitors, leading to renal insufficiency .…”
Section: Discussionsupporting
confidence: 90%
“…B, Blsulfite modifications of DNA compared to initial nuclaotide sequences. C, Sequencing results photoperiod 12 ; GPR54/Kiss are expressed on GnRH and kisspeptin neurons in the hypothalamus and simultaneously belong to the upstream genes of GnAQ in the GnRH signaling pathway, which are also major regulators of the HPG axis, consistent with the results of this study. In the GnRH signaling pathway, GnAQ acts as a downstream gene of the GnRH receptor and is directly affected by this receptor; the downstream genes of PLC and PRKCB can combine with nerve calcium-regulating protein inhibitors, leading to renal insufficiency.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations